Geopolitics of sensing and knowing: On (de)coloniality, border thinking, and epistemic disobedience - Walter Mignolo (Linköping University Electronic Press, 2013)
Decoloniality is, in the first place, a concept whose point of origination was the Third World. Better yet, it emerged at the very moment in which the three world division was collapsing and the celebration of the end of history and a new world order was emerging. The nature of its impact was similar to the impact produced by the introduction of the concept of "biopolitics", whose point of origination was Europe. Like its European counterpart, "coloniality" moved to the center of international debates in the non-European world as well as in "former Eastern Europe." While "biopolitics" moved to center stage in "former Western Europe" (cf., the European Union) and the United States, as well as among some intellectual minorities of the non-European followers of ideas that originated in Europe, but who adapt them to local circumstances, "coloniality" offers a needed sense of comfort to mainly people of color in developing countries, migrants and, in general, to a vast quantitative majority whose life experiences, long and short-term memories, languages and categories of thoughts are alienated to life experience, long and short-term memories, languages and categories of thought that brought about the concept of "biopolitics" to account for mechanisms of control and state regulations.